1984
DOI: 10.1139/o84-089
|View full text |Cite
|
Sign up to set email alerts
|

The induction of α-amylase by starch in Aspergillus oryzae: evidence for controlled mRNA expression

Abstract: The induction of alpha-amylase by starch has been studied in the filamentous fungus Aspergillus oryzae. Low levels of alpha-amylase activity were found in both intracellular and extracellular samples from glucose-grown cultures. However, alpha-amylase activity increased when starch was the sole carbon source. The intracellular enzyme activity was induced by a factor of approximately 6.5, while the extracellular activity increased 20-fold over that found in the glucose-grown cultures. Regardless of the carbon s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
7
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 1 publication
4
7
0
Order By: Relevance
“…Ethidium bromide staining showed that almost the same amounts of RNA were present in each sample. This result confirmed that the production of T AA is controlled at a transcriptional level, consistent with the result from an in vitro translation experiment (Erratt et al, 1984).…”
Section: Lag Ssupporting
confidence: 90%
“…Ethidium bromide staining showed that almost the same amounts of RNA were present in each sample. This result confirmed that the production of T AA is controlled at a transcriptional level, consistent with the result from an in vitro translation experiment (Erratt et al, 1984).…”
Section: Lag Ssupporting
confidence: 90%
“…5) Of the 300 -amylases known to date, Takaamylase A (TAA), secreted by Aspergillus oryzae, is one of the best studied in terms of catalytic and gene regulatory functions. [6][7][8][9][10][11][12] TAA is also the first -amylase to have its three dimensional structure determined by Xray diffraction. 13) The bioconversion of starch into ethanol is a two-step process: the first step is saccharification, where starch is converted into sugar by an amylolytic microorganism or enzymes such as -amylase and glucoamylase, and second step is fermentation, where sugar is converted into ethanol, mostly by yeasts.…”
mentioning
confidence: 99%
“…The combined information from these experiments allows us to hypothesize the genesis of the 146-kDa extracellular glucoamylase. As in previous work on the a-amylase of Aspergillus oryzae (8,11) and cellulase of Schizophyllum commune (37,38), there is no doubt that expression of glucoamylase is highly regulated in response to its source of carbohydrate and that this regulation is primarily at the level of mRNA transcription and stability. The immunoprecipitation of the glucoamylase-related translation product made in a rabbit reticulocyte cell-free system revealed that the nascent glucoamylase precursor is approximately 120 kDa (±+7%) in size.…”
Section: Resultsmentioning
confidence: 61%